Practical irrigation flow measurement and control - an update - Replogle, John A., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Previous discussions concerning practical technologies that can encourage farmers to adopt practices supporting sustainable irrigated agriculture are updated. Important among these are convenient water measurement and control techniques. These techniques need to be available not only to the farmers, but also to the delivery system operators that make the system responsive to the on-farm needs. Improved irrigation planning and management techniques depend heavily on accurately controlling and quantifying water deliveries. Automation places a further burden on reliable operation of primary water measuring and flow control equipment. Many simple constructions and operating procedures can be provided to farmers and irrigation-delivery-system operators that offer considerable convenience at small expense and can be included in automation upgrades to improve reliability. Problems of reliability are aggravated if equipment is not easily field checked for proper functioning. Many observable clues, when they do exist, go unrecognized by inadequately trained personnel. This compilation of practices and design suggestions should help the operator assure valid measurement data and control functions. These suggestions are intended to make these devices easier to use, easier to verify, and more economical to construct and install. The techniques and devices discussed included: (a) accurate and convenient zero setting for weirs and flumes; (b) pressure-transducer field checks; (c) easy-to-use scales for orifice and Venturi meters; (d) wave suppressors for canals that flow at variable depths; (e) method for measuring Manning n values; and (f) flow-profile visualization using rising-bubble techniques to evaluate canal flow conditioning. Also included is a discussion of some pipe flow conditioning ideas used in field practice for devices installed in adverse conditions.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.